Der Aufstieg Chinas: Innerchinesische und internationale Herausforderungen - Heberer, Thomas; Senz, Anja-Désirée (Zeitschrift für Außen- und Sicherheitspolitik, 2018)
On the occasion of China’s 40th anniversary of initiating reform policies this article reflects on the results of this reform. Moreover, in respect to its current domestic and foreign policies it examines China’s international position and its possible consequences for Europe. In 2017, China has put forward a road map for its modernizing processes: creating a comprehensive modernized country and achieving world power status until 2050. Concurrently, a readjustment of China’s foreign and security policies has been initiated which shall correspond to China’s growing role and its development into achieving great power status. In addition, the increasing tension between China and the US and its possible consequences are examined.